GAMBARAN TINGKAT PENGETAHUAN, SIKAP DAN PERSONAL HYGIENE SAAT MENSTRUASI PADA REMAJA PUTRI - Ulfa Diya Atiqa; Syamsuriah (Bajang Institute, 2024)
Adolescence is the period of development between childhood and maturity. Menstruation is just one of the many changes that occur throughout this period. Menstrual hygiene management is necessary to avoid infections that can harm the reproductive organs. The purpose of this study is to determine the knowledge, attitudes, and management of menstruation hygiene among adolescent females in Tinambung District. This quantitative study, which used a cross-sectional design, was carried out in May 2020. The participants in this study were adolescent girls from Tinambung District, Polewali Mandar. The study's sampling population was 250 adolescent girls. The proportionate random sampling method was used. According to the results of this survey, 39.2% of female students had good menstrual hygiene, 40.9% had a positive attitude toward menstrual hygiene, and 39.2% knew how to manage their menstrual hygiene. Efforts need to be made to improve reproductive health counseling to assist adolescent females in maintaining great menstrual hygiene.